Implementasi Pelayanan Hak Tanggungan Elektronik Bagi Kreditor dan Pejabat Pembuat Akta Tanah - Pandam Nurwulan (Fakultas Hukum Universitas Islam Indonesia, 2021)
Electronic Mortgage Services since 8th of July 2020 have been implemented simultaneously without going through an adequate transition and socialization period, which raises problems for its users. This research examines, first, how is the implementation of the electronic mortgage service mechanism for Creditors and PPAT? second, how to solve the obstacles faced by users of Electronic Mortgage services. This is a normative legal research supported by information from informants, namely electronic mortgage users, legal materials processing and qualitative descriptive analysis. From this research, it can be concluded that first, the mechanism for implementing Electronic Mortgage services begins with the making and inauguration of APHT by PPAT, registered with the Land Office online and the Mortgage Certificate requested and printed by the recipient of the Mortgage Rights. Second, solving the obstacles faced by Electronic Mortgage Users refers to the Technical Guidelines made by the ATR Ministry on April 29, 2020, because basically the obstacles are mostly related to IT systems and Electronic HT Service servers. HT-e users must confirm the problem to the service provider, namely the local Land Office. Users must be skilled in using the tools to complete the Granting of Mortgage Rights until the Electronic Mortgage Certificate is issued.